Réponses

Meilleure réponse !
2014-01-24T07:50:21+01:00
A= 2/3-3 / 1-2/9
A = (2/3 - 3 x 3 / 1 x 3) : (1 x 9 / 1 x 9 - 2/9)
A = (2/3 -9/3) : (9/9 - 2/9)
A = -7/3 : 7/9
A = -7/3 x 9/7
A = -63/21
A = -21 x 3 / 21 x 1
A = -21/1

B = 2/5 +3/5 : ( 1 - 10)
B = 2/5 + 3/5 : 9
B = 5/5 : 9/1
B = 5/5 x 1/9
B = 5/45
B = 5 x 1 / 5 x 9
B = 1/9

C = 5 + ( 1/8 + 1) : 3/4

C = 5 + (1/8 + 1 x 8 / 1 x 8) : 3/4
C = 5 + (1/8 + 8/8) : 3/4
C = 5 + 9/8 : 3/4
C = 5 + 9/8 x 4/3
C = 5 + 36/24
C = 5 x 24 / 1 x 24 + 36/24
C = 120/24 + 36/24
C = 156/24
C = 12 x 13 / 12 x 2
C = 13/2